Shape of prismatic dislocation loops in anisotropic -Fe - Fitzgerald, S; Yao, Z (2009)
Prismatic dislocation loops are the primary manifestation of radiation damage in crystals, and contribute to the phenomenon of radiation embrittlement. This undesirable effect, most serious for materials used in high-dose environments such as next-generation fission and future fusion reactors, results from the strong interaction between gliding dislocations, the carriers of plasticity, with the population of radiation-induced prismatic loops. Ferritic-martensitic steels, the most promising candidate materials for future high-dose applications, are based on iron and are known to become highly elastically-anisotropic at the high temperatures (500C) at which they must operate. In this article, we develop a novel modelling approach based on anisotropic elasticity theory to predict the shapes of prismatic loops in anisotropic crystals, paying particular attention to the technologically important case of -iron. The results are compared with transmission electron microscope observations of the damage structure sustained by ultra-high-purity iron irradiated to a dose of approximately two displacements per atom.